2018
DOI: 10.1111/iju.13849
|View full text |Cite
|
Sign up to set email alerts
|

Green tea intake and risk of incident kidney stones: Prospective cohort studies in middle‐aged and elderly Chinese individuals

Abstract: Objectives To investigate the association between green tea intake and incident stones in two large prospective cohorts. Methods We examined self‐reported incident kidney stone risk in the Shanghai Men's Health Study (n = 58 054; baseline age 40–74 years) and the Shanghai Women's Health Study (n = 69 166; baseline age 40–70 years). Information on the stone history and tea intake was collected by in‐person surveys. Multivariable Cox proportional hazards models were adjusted for baseline demographic variables, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…In the present study, tea drinking was shown to affect urinary stone formation, which was contrary to our previous finding that long-term consumption of tea increased the risk of stone formation due to an increased intake of oxalate [14]. Also, recent studies have shown the beneficial effects of tea consumption on the prevention of stone formation [1517]. Southern China is a tea-growing area, and tea consumption is high.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, tea drinking was shown to affect urinary stone formation, which was contrary to our previous finding that long-term consumption of tea increased the risk of stone formation due to an increased intake of oxalate [14]. Also, recent studies have shown the beneficial effects of tea consumption on the prevention of stone formation [1517]. Southern China is a tea-growing area, and tea consumption is high.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Rode et al73 found that drinking green tea significantly reduced the prevalence of COM stones in 273 high-calcium kidney stones. Shu et al74 surveyed the history of 319,211 Shanghai men (n=58,054; baseline age of 40–74 years) and 696,950 Shanghai women (n=69,166; baseline age of 40–70 years) tea intake information. The results showed that the intake of green tea was associated with a lower risk of developing kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in two other animal studies, the administration of catechins or green tea prevented crystallization, especially monohydrate CaOx crystal deposits within tubular lumen [ 22 , 23 ]. However a recent study in a very large prospective Chinese cohort reports that green tea intake was associated with a lower risk of incident kidney stones [ 27 ]. Our results are in accordance with these findings and suggest that drinking daily green tea (assessed by a detailed survey) would not be detrimental in both sexes.…”
Section: Discussionmentioning
confidence: 99%